E0396 Clinical analysis of 30 individuals with micro CK type 1. (17th November 2010) - Dong, Zhi-Yuan; Wang, Zhi-kai; Liu, Ji-Yong; Tang, Xiao-Bin; Wang, Li-Mei; Shi, Lian-Yi; Liu, Yuan-Ying; Zhao, Xiu-Zhen
Abstract : Objective: The aim of the prospective study was to investigate the clinical and laboratory features of individuals with micro creatine kinase type 1 (MCK-1), and to evaluate the clinical significance of these cases who expressed serum MCK-1. Methods: To screen MCK-1individuals from serum samples in our biochemistry laboratory from April 2002 to April 2010 according to both increasing CK-MB activity and CK-MB/CKratio over 25%, and finally confirmed by agarose gel electrophoresis of CK isoenzyme analysis. To analyse the clinical and laboratory data of individuals who expressed serum MCK-1 isoenzyme. Results: MCK-1 was detected in the samples from 30 subjects. Their mean age at the initial presentation was 58.6 years (range 26 to 81), 63.3% were female (n=19), and 39.3% (n=11) had hypertension.of the 30 subjects, 10 (33.3%) had increased total CK activity, and 7 (23.3%) showed the abnormal phenomenon that CK-MB:CK ratio was >1. Our study indicated that the misdiagnostic rate was 40.0 % (n=12), and the rate of missed diagnosis was 46.7% (n=14). There were 3 deaths during the follow-up period. Conclusion: MCK-1 was not rare in clinical practice. Among the conditions in which CK-MB activity is elevated in the absence of myocardial injury or infarction using immunoinhibition methods, MCK-1 merits special attention from clinicians. CK-MB index is a simple and rapid screening test for MCK-I.